2009
DOI: 10.1016/j.expneurol.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and toxicodynamics of paraquat accumulation in mouse brain

Abstract: Paraquat (PQ) is a potential human neurotoxicant and is used in models of oxidative stress. We determined the toxicokinetics (TK) and toxicodynamics (TD) of PQ in adult mouse brain following repeated or prolonged PQ exposure. PQ accumulated in different brain regions and reached a plateau after ~18 i.p. (10 mg/kg) doses and resulted in modest morbidity and mortality unpredictably associated with dose interval and number. PQ had divergent effects on horizontal locomotor behavior depending on the number of doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 33 publications
(50 reference statements)
5
67
5
1
Order By: Relevance
“…It is known that alterations in DA levels in the striatum of WT animals require 12-18 doses of 10 mg kg 21 PQ (Prasad et al, 2009;Thiruchelvam et al, 2000), or combinations of PQ with MPTP or Maneb (Shepherd et al, 2006;Thiruchelvam et al, 2000). In our study, neither DA nor its metabolites change in the WT cohort after the 7th dose.…”
Section: Apod-ko Mice Show Alterations In the Dopaminergic System Asscontrasting
confidence: 54%
See 2 more Smart Citations
“…It is known that alterations in DA levels in the striatum of WT animals require 12-18 doses of 10 mg kg 21 PQ (Prasad et al, 2009;Thiruchelvam et al, 2000), or combinations of PQ with MPTP or Maneb (Shepherd et al, 2006;Thiruchelvam et al, 2000). In our study, neither DA nor its metabolites change in the WT cohort after the 7th dose.…”
Section: Apod-ko Mice Show Alterations In the Dopaminergic System Asscontrasting
confidence: 54%
“…PQ and other neurotoxicants have been used as chemical models of Parkinson's disease. We used a paradigm of PQ injections (see Methods) that generates a mild OS and slow PQ accumulation in the brain (Prasad et al, 2009), but not systemically (Prasad et al, 2007). With this low-dose chronic PQ exposure, ApoD mRNA levels in the WT 1554 BAJO-GRAÑERAS ET AL.…”
Section: Apod-ko Mice Show Alterations In the Dopaminergic System Assmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraquat (PQ) (1,1-dimethyl-4-4-bipyridynium dichloride) (PQ), is widely used as herbicide. In vivo studies employing Drosophila melanogaster [5], Rattus norvegicus [6] and Mus musculus [7] have revealed that PQ is neurotoxic which affects dopaminergic neurons. The toxicity of PQ is a consequence of generation of ROS mainly hydrogen peroxide and hydroxyl radical [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that compensatory/ buffer downstream processes provoked by soma loss, variations in experimental design (e.g. route of administration, dosing regimen, sacrifice interval, striatal subregions tested, age of mice) can possibly contribute to some of the inconsistency observed across studies (Rojo et al, 2007;Prasad et al, 2009;Kang et al, 2010;Rappold et al, 2010). …”
Section: Weight Of Evidence For the Ker Biological Plausibilitymentioning
confidence: 99%